Clinical aspects of functional foods and nutraceuticals [ - Bagchi, Debasis , 1954-; Ghosh, Dilip Kumar; Konishi, Tetsuya (Boca Raton, Florida : CRC Press, 2015)
In the last three decades, revolutionary achievements have taken place in nutraceutical and functional food research including the introduction of a number of cutting-edge dietary supplements supported by human clinical trials and strong patents. Novel manufacturing technologies including unique extraction processes, bioavailability improvements through delivery technologies such as nanotechnology, and innovative packaging have been critical steps for their successful positioning in the marketplace and consumer acceptance worldwide. Nonetheless, mixed messages have emerged from
1. Introduction -- 2. Science underpinning health benefits -- 3. Problems and challenges to industries, consumers, and policy makers -- 4. Innovation versus regulation -- 5. Farm to clinic approach/functional aspects of food factors
Includes index
Keywords: Dietary supplements -- Standards; Food industry and trade -- Quality control; Functional foods -- Standards